Study protocol for the Health Outcomes in Pregnancy and Early Childhood (HOPE) Study: A mother-infant study in American Samoa - Lacey W. Heinsberg; Miracle Loia; Susie Tasele; Kima Faasalele-Savusa; Jenna C. Carlson; Scott Anesi; Katie Desobry; Efren Yuchongco; Brian Fortuno Guevara; Aigaeiva Sesaga; Alice Iloilo; Va’atausili Tofaeono; et al. (PLoS ONE, 2025)
Pacific Islanders, including those in American Samoa, face a disproportionately high burden of gestational diabetes mellitus (GDM) and related sequalae of metabolic conditions. The CREBRF rs373863828 genetic variant, which is uniquely common among Pacific Islanders, has been paradoxically associated with higher body mass index (BMI) but lower risk of type 2 diabetes. While emerging evidence suggests this variant may influence both maternal metabolic outcomes and infant growth, studies in pregnancy and early life remain limited. The purpose of this paper is to describe the protocol for a study designed to address these gaps. The Health Outcomes in Pregnancy and Early Childhood (HOPE) Study is an observational, longitudinal cohort study that will enroll up to 180 Samoan pregnant women and their infants (target n = 150 dyads completing study protocols) in American Samoa, with follow-up through six months postpartum/postnatal. The study includes questionnaires, anthropometric measurements, and biospecimen collection. Genetic and epigenetic analyses will examine associations between maternal and infant CREBRF rs373863828 genotype, gestational diabetes status, infant body size, and cord blood DNA methylation. The study is approved by the Institutional Review Boards at the University of Pittsburgh, Yale University, and the American Samoa Department of Health, as well as the Lyndon B. Johnson Tropical Medical Center (American Samoa) Research Oversight Committee. Findings will be disseminated through peer-reviewed publications, conference presentations, and community reports.